(untitled) (LACCEI, 2024)
The use of conventional energy sources represents a problem due to its high GHG emission, therefore the implementation of renewable energy resources manifests a solution to this problem. The course work was developed in the city of Arequipa taking into account the conditions present in the city, with the main objective of determining the kg of CO2 eq that were not emitted through the use of photovoltaic panels. For this, the sampling of twenty-two students from the San Pablo Catholic University was carried out, in this way the electrical consumption of each one was obtained, later the energy produced by each source presented in the Peruvian electrical matrix was calculated, which allowed determining the emissions of GHG for each source working them in kg of CO2 eq. Following this, the electrical production of the photovoltaic panel was evaluated, making use of the NASA POWER online program and the equations proposed in the article. Finally, it was obtained as a result that the implementation of photovoltaic panels managed to satisfy the electrical consumption in its entirety for seven students, while for the other fifteen it was possible to partially satisfy their consumption. Likewise, a significant reduction in GHG emissions was evidenced, going from 287.17 kg of CO2 eq to 119.74 kg of CO2 eq, which represented a reduction of 39.77%.